The Influence of Attitude, Knowledge and Skill on Discipline and its Impact on the Performance of the Employees of the Anambas Islands Transportation Department - Zanjjie, Syakdun; Juniarti, Atty Tri; Ratnamiasih, Ina (Transforma Jurnal Manajemen, 2023)
The purpose of this research is to find out how the influence of work attitude, work knowledge, and work skills on work discipline and its effect on employee performance. This study uses quantitative analysis with descriptive and verification methods (path analysis) to determine the condition of the variables and the relationship between the variables studied, so as to produce conclusions that will clarify the object of research. The population in this study were all employees at the Anambas Islands Regency Transportation Service, totaling 281 people. Respondents in this study were selected through the Proportional Certified Random Sampling technique and determining the number of samples using the Slovin technique formula. Based on calculations, the sample who became respondents in this study were 80 people. The findings of this study are that partially all independent variables have a significant positive effect. The effect of attitude on employee work discipline is 35.58%, the effect of work knowledge on employee work discipline is 21.72%, the effect of skill on employee work discipline is 29.74%, and simultaneously the total effect of attitude, knowledge and work skills on employee work discipline of 87.04%, while the influence of other variables outside the variables not examined is 12.96%, and the effect of work discipline on employee performance is 78.00%.